2020
DOI: 10.1002/bit.27613
|View full text |Cite
|
Sign up to set email alerts
|

Scaffolds obtained from decellularized human extrahepatic bile ducts support organoids to establish functional biliary tissue in a dish

Abstract: Biliary disorders can lead to life‐threatening disease and are also a challenging complication of liver transplantation. As there are limited treatment options, tissue engineered bile ducts could be employed to replace or repair damaged bile ducts. We explored how these constructs can be created by seeding hepatobiliary LGR5+ organoids onto tissue‐specific scaffold. For this, we decellularized discarded human extrahepatic bile ducts (EBD) that we recellularized with organoids of different origin, that is, live… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 29 publications
1
21
0
Order By: Relevance
“…These empty scaffolds were created as a model for bile duct damage using a method called decellularization. 26 We demonstrate that recellularization by BCOs results in the formation of a confluent monolayer with cholangiocyte‐like cells. Importantly, BCOs are less proliferative as well as lose their LGR5 expression when cultured upon EHBD scaffolds.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…These empty scaffolds were created as a model for bile duct damage using a method called decellularization. 26 We demonstrate that recellularization by BCOs results in the formation of a confluent monolayer with cholangiocyte‐like cells. Importantly, BCOs are less proliferative as well as lose their LGR5 expression when cultured upon EHBD scaffolds.…”
Section: Discussionmentioning
confidence: 67%
“…Since we recently showed that our repopulated scaffolds with BCOs are properly polarized by cilia staining and that they become functional constructs by demonstrating transepithelial electrical resistance (TEER) and ion‐channel functionality, 26 the next goal would be to create a 3D construct. Cholangiocyte‐organoids cultured in non‐canonical WNT‐stimulated conditions have previously shown feasibility to repopulate 3D constructs and function as EHBD in vivo.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additives enhance the contact between the matrix and organoids and enhance some properties of the hydrogel, which are more conducive to the formation and development of organoids. 2) The hydrogel has a structure similar to that of the environment in vivo , such as the decellularized matrix of homologous tissue ( Giobbe et al, 2019 ; Mollica et al, 2019 ; Bi et al, 2020a ; Bi et al, 2020b ; Meran et al, 2020 ; Willemse et al, 2021 ), a culture hydrogel of intestinal organs composed of a collagen V-coated porous substrate, and a collagen I gel overlay ( Tong et al, 2018 ); 3D collagen type I scaffolds mimicking the double cortical layer ultrastructure of the thymus ( Bortolomai et al, 2019 ). Different tissues have different structures.…”
Section: Challenges and Breakthroughsmentioning
confidence: 99%
“…SOX17) and gained expression of intrahepatic cholangiocyte-related genes (SOX4). Whether this plastisity is also observed when intrahepatic cholangiocyte organoids engraft downstream was not shown, however a recent in vitro study demonstrated that repopulation of the extrahepatic bile duct matrix by intrahepatic cholangiocyte organoids was less profound than their extrahepatic counterparts (7). Interestingly, when freshly isolated human cholangioctes were infused limited engraftment and survival benefits were observed.…”
Section: Accepted Articlementioning
confidence: 99%